Association of socio-demographics and home food environment factors on body weight status among primary school children - Rathuan, Rina Syahira; Zalbahar @ Zabaha, Nurzalinda; Sulaiman, Norhasmah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Obesity in children is a global epidemic issue. Home food environment is an important aspect that may influence children’s body weight status. The aim of this study is to identify the association between socio-demographics and home food environment (HFE) factors with body weight status in primary school children in Bangi, Selangor. Methods: There were 398 children (43.5% males and 56.5% females) aged 7-11 years old (mean age of 9.04±1.41 years) and their parents (66.6% mothers and 33.4% fathers) from eight randomly selected primary schools participated in this study. Parents were asked to complete a self-administered questionnaire on socio-demographic background, feeding practices and food availability, while children were interviewed to obtain information on parental styles and physical activity level. Weight and height of children were assessed, and BMI-for-age z-score (BAZ) was calculated by using WHO Anthroplus Software. Results: Overweight and obesity prevalence was 17.8% and 13.1% respectively. A majority of the parents (61.3%) in this study practiced authoritative parenting style. The increased odds of childhood obesity has been found to be associated with an increasing age (OR=1.239, p<0.05). The risk for overweight or obese was greater for male students than for female students (OR=1.619, p<0.05). Parent’s increasing restriction for weight control (OR=1.080, p<0.05) and decreasing pressure to eat (OR=0.913, p<0.05) increased childhood overweight and obesity risk. Conclusion: This study emphasizes the importance of involving parents in the obesity intervention programs for children.